PERTANGGUNGJAWABAN PIDANA KOPERASI DALAM TINDAK PIDANA MELAKUKAN KEGIATAN PERBANKAN TANPA IJIN - Oktaviani Suendra, Dessy Lina (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015), 2015)
Cooperative in Indonesia today is inseparable from the possibility of a criminal act, one criminal offense related banking licenses. Conflicts occur in the setting of norms of criminal responsibility in the cooperative banking activities without a license, where the Cooperatives Act only regulates the sanctions administrtif for cooperatives, but cooperative management is not subject to criminal sanctions, while the Banking Act regulated the criminal sanctions for the management / leadership of the cooperative. Based on this background, the didapatlah formulation of the problem, namely: 1) How is criminal responsibility in case of banking criminal acts without permission undertaken by cooperatives 2) Who is responsible for committing a crime when the cooperative banking without permission.This research is a normative legal research. The data used in this study include primary and secondary data. Data collection techniques used is literature study technique using a systematic method through the card system. Legal materials analysis techniques used are descriptive analysis technique, argumentation technique, interpretation and analysis techniques. Of overall relevant data will be processed and analyzed in a way compiling such data systematically and selectively, then the data is analyzed in terms of the descriptions are accompanied by an explanation of the theories of law. These results indicate that the cooperative actions that can be accounted for criminal is a criminal offense embezzlement, criminal fraud, banking criminal acts and corruption. As for the banking criminal acts that can be performed by the cooperative is a criminal offense related banking licenses, in which for the moment in its criminal liability still refers to the Banking Act which provide criminal sanctions for those who give orders / leader. While the parties responsible for committing a crime if the cooperative banking without permission is a cooperative management.
Keywords: Cooperative; Criminal Liability; Banking Crimes Without Permission